Morimura Yasumasa : Self-portrait as art history. - Hayashi, Yoko; Junichi, Shioda; Obigane, Akio (Tokyo : Museum of Contemporary Art, 1998)
Comprised of two volumes, this material was published in conjunction with the exhibition of the same title. As mentioned in the foreword by the organizers, this was the first retrospective exhibition with a special focus on the Art History series which forms the core of MORIMURA’s oeuvre. Vol.1 includes essays, biography, bibliography and list of works. ‘An Irregular Interview, or Monologue by Morimura Yasumasa,” edited by Shinji KOHNO is based on taped artist’s monologue. In recording the monologue, KOHNO selected twenty one key words that would help understanding MORIMURA’s oeuvre, to which MORIMURA gave his thoughts. KOHNO selected the key words based on the several interviews he had with the artist between October 1997 and February 1998. The key words are as follows: slow, wait, work hard, old-fashioned, art, beautiful, entertainment, wear, grand romance, survival, self, folie, similarity, love, laugh, escalate, actress, defense/ self-portrait/ eyes, daughters of art history, photography/ painting, performance.
Morimura Yasumasa : Self-portrait as art history, Museum of Contemporary Art, Tokyo, 07.06 - 30.08.1998
biografie
Engels
Japans
kunstcatalogus
Keywords: Morimura, Yasumasa